Central Adiponectin Induces Trabecular Bone Mass partly through Epigenetic downregulation of Cannabinoid Receptor CB1 - Jiang, Hua (J Cell Physiol, 2018)
Central adiponectin (APN) in either the globular (gAPN) or full-length (fAPN) forms decrease sympathetic tone and increase trabecular bone mass in mice through the hypothalamus. It is known that cannabinoid type-1 (CB1) receptors are expressed in the hypothalamic ventromedial nucleus (VMN) and participate in energy metabolism by controlling sympathetic activity. However, whether central APN could influence endocannabinoid signaling through CB1 receptor to regulate bone metabolism has not been characterized. Here we demonstrate that gAPN down-regulated CB1 expression in embryonic mouse hypothalamus N1 cells in vitro. gAPN intracerebroventricular (icv) infusions also decreased hypothalamic CB1 expression and bone formation parameters in APN-knockout (APN-KO) and wild-type (WT) mice. Most importantly, mice pretreated with icv infusions with the CB1 receptor agonist arachidonyl-2′-chloroethylamine (ACEA) or antagonist rimonabant attenuated or enhanced respectively central APN induction of bone formation. We then investigated whether epigenetic signaling mechanisms were involved in the downregulation of hypothalamic CB1 expression by gAPN. We found gAPN enhanced expression levels of various histone deacetylases (HDACs), especially HDAC5. Furthermore, chromatin immunoprecipitation assays revealed HDAC5 bound to the transcriptional start site TSS2 region of the CB1 promoter. In summary, our study identified a possible novel central APN-HDAC5-CB1 signaling mechanism that promotes peripheral bone formation through epigenetic regulation of hypothalamic CB1 expression.